Towards cultural transformation : Culture as planetary well-being - Koistinen, Aino-Kaisa; Kortekallio, Kaisa; Santaoja, Minna; Karkulehto, Sanna (Routledge, 2025)
Culture covers myriad aspects of human life. Most often it is understood as intellectual or artistic practices, but in a broader view, culture covers the habits, lifestyles, traditions, beliefs, values, and worldviews that shape human lives and societies. Culture also undergoes continuous change and is affected by human actions. Current ecological and well-being crises caused by destructive cultural practices and actions pose an existential risk to both humans and nonhumans. This chapter argues that when challenging, preventing, and changing such destructive human practices and actions, the role of culture is indispensable. Building on and rethinking cultural sustainability, the chapter outlines how culture could be transformed into and regarded as planetary well-being—a process in which culture shifts towards more sustainable practices and actions that enable well-being for humans and nonhumans alike. The chapter focuses on the potential of contemporary art in fostering this kind of transformation.
Interdisciplinary Perspectives on Planetary Well-Being